(untitled) (Global Conference on Medical and Health Sciences, 2026)
Smart surgical navigation systems have emerged as a critical innovation in modern neurosurgery, enabling real-time integration of imaging data with intraoperative guidance to enhance surgical precision and adaptability. Traditional navigation systems rely on preoperative imaging, which may become inaccurate due to intraoperative anatomical changes such as brain shift. The integration of real-time imaging modalities—including intraoperative MRI, ultrasound, and advanced optical tracking—addresses these limitations by providing dynamic and continuously updated anatomical information.